Membincang Ulang Komentar Nabi Tentang Wilayat Al-Mar'ah - Abdul Wahab (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2018)
The study of wilāyat al-mar'ah is interesting to be explored given the many rigid interpretations of the hadith of the Prophet so as to imply discredit the ability of women. Through the language and historical analysis of the hadith of the prophet concerning wilāyat al-mar'ah it is found that: a) in the language perspective, the hadith about wilāyāt al-mar'ah can be interpreted that until whenever a people (wherever) will not succeed or prosper when handed over their (power) affairs to women (anywhere) to play a central role; b) The Prophet's comment on